Land Degradation Neutrality: Concepts and Implementation Mechanism - Ajai; Bhatnagar, Rimjhim; Arya, Ashutosh S. (Annals of Arid Zone, 2024)
All forms of life on Earth depend on ‘land’ through varied means, such as finding habitats, getting the right environment for human beings to survive, using land as substrate for agriculture etc. In the recent times, land-based ecosystem goods and services have gone to unprecedented levels of land exploitation causing a sharp increase in the process of land degradation. About one-third of the global land surface has been affected by desertification and land degradation (DLD). More than 100 countries, comprising of about 2.6 billion people are under the effect of DLD-directly or in directly. In Asia alone, 38 out of 48 countries are affected while in India, about 32% of its geographical area is undergoing the process of DLD. The present paper discusses the fundamental concepts of land degradation, its causes and drivers and methods to mitigate it. National, regional and global efforts on mapping, monitoring and assessment of land degradation have been reviewed. United Nation’s Land Degradation Neutrality (LDN) program, its conceptual framework and its implementation mechanisms in India has been discussed in detail.